Interleukin 1 regulates human metallothionein gene expression. - Karin, M (1985)
Incubation of cultured human cells with interleukin 1 leads to increased expression of the human metallothionein-IIA gene. Recently, metallothionein has been shown to be an efficient free radical scavenger, and induction by interleukin 1 may be part of a protective response to minimize damage by hydroxyl radicals.